FREQUENCY OF CONTRACEPTIVE USAGE AMONG PAROUS WOMEN ATTENDING TERTIARY CARE HOSPITAL IN HYDERABAD - Aslam, Amna; Zaki, Nida; Samoon, Hina; Shams, Nahil (Annals of Allied Health Sciences, 2025)
Objective: To determine the frequency of total contraceptive usage and various contraceptive methods usage among parous women attending Isra University Hospital Hyderabad. Material & Methods: A cross-sectional study was conducted at Isra University Hospital Hyderabad from 1st January 2023 to 31st May 2024.Total 375 women were included fulfilling the inclusion and exclusion criteria. Informed consent was taken from all women. History regarding contraception was taken and all the data regarding demographic variables & contraceptive usage among parous women were entered in the predesigned Questionnaire. The data was filled out by face-to-face interview. Data was analyzed using SPSS version 28. Results: Mean age of participants was 36.5+5.15 years. 197 (52.53%) women were using contraception, while 178 (47.47%) were not using any contraceptive. Women residing in rural locality were significantly found associated with non-usage of contraception (p-value 0.001). Non usage of contraception was significantly found in Illiterate and lower educational status women (p-value 0.001). It was found that contraceptive usage was more in Multiparous 111 (56.34%) and grand -multiparous women 71(36.04%), while only few primiparous women 15(7.62%) had history of contraceptive usage. Conclusion: It is concluded that more than half of women had history of contraceptive usage. Poor socioeconomic status and lower educational level were resulting in non-usage of contraceptives.